Exploring the Lived Experiences of 911 Dispatchers: A Phenomenological Study - Stanley, Dawson; Manning, LaShondra (Canadian Journal of Counselling and Psychotherapy, 2023)
Among the first responder profession, 911 dispatchers are considered the first point of contact for those in crisis. Despite existing literature concluding that 911 dispatchers experience rates of traumatic exposure similarly to other emergency service personnel, there is limited research regarding this population’s specific experiences. The purpose of this study was to explore the lived experiences of 911 dispatchers to determine the consistency of their experiences with the limited existing literature. In this international study, a transcendental phenomenological research approach was utilized to describe the lived experiences and commonalities of the participants. Based on the findings from this study, five prominent themes emerged: (a) health issues, (b) trauma reactions, (c) strained interpersonal relationships, (d) job dissatisfaction, and (e) resilience. Limitations, recommendations for future research, and implications related to the counselling setting are discussed.